2000
DOI: 10.1352/0895-8017(2000)105<0032:mocifc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Models of Child–Family Interactions for Children With Developmental Delays: Child-Driven or Transactional?

Abstract: Child-driven and transactional models of child-family interactions were tested with 80 children who had developmental delays and their families. Children's cognitive competence, personal-social competence, behavior and communication "hassle," and family accommodations to the children were assessed at child ages 3, 7, and 11. Accommodations were summarized as internal (within the family) and external (use of outside resources) intensity and types. Results indicate that the longitudinal relationships between chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 0 publications
1
43
0
1
Order By: Relevance
“…First, children with delays who also exhibited significant behavior problems were excluded from this study; yet they constitute approximately 25% of this population and create considerable parental stress (Baker et al, 2003) and control problems (Keogh, Garnier, Bernheimer, & Gallimore, 2000). Similarly, gender may well exert an effect, but differences could not be examined because of the relatively small number of girls in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…First, children with delays who also exhibited significant behavior problems were excluded from this study; yet they constitute approximately 25% of this population and create considerable parental stress (Baker et al, 2003) and control problems (Keogh, Garnier, Bernheimer, & Gallimore, 2000). Similarly, gender may well exert an effect, but differences could not be examined because of the relatively small number of girls in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research suggests that changes in parenting behaviors and parent-child interactions may be brought about by parental distress resulting from the child's condition (Quittner, Opipari, Regoli, & Jacobsen, 1992), by parental perceptions of the child (Holmbeck et al, 2002;Stern, Karraker, Sopko, & Norman, 2000), or as a result of the child's behavior, specifically, his or her need for structure and cognitive support (Keogh, Garnier, Bernheimer, & Gallimore, 2000;Landry et al, 1990). The literature on bonding and attachment suggests that maternal depression disrupts the natural reciprocity between parent and child (Tronick & Weinberg, 1997).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…In fact, several studies have found parent-child interactions to be more related to child characteristics than parent characteristics. In a study of young children with developmental delays, Keogh et al (2000) found that the frequency and intensity of accommodations to the child's disability were related to the characteristics of the child, such as the need for frequent monitoring, rather than SES or maternal education. Similarly, Landry et al(1990) found that mothers of very-low-birth-weight toddlers were more likely to direct their children, whereas mothers of full-term children were more likely to use suggestions, even after controlling for child IQ and maternal education.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Given the strong correlation between child behavior problems and parental wellbeing depicted above and available prospective studies showing that parental stress may be child-driven [39], interventions which improve the child's functioning can be expected to decrease the parents' strain. A detailed review of treatment recommendations for individuals with FXS was presented by Hills-Epstein et al [40].…”
Section: Interventions To Reduce Caregiver Burdenmentioning
confidence: 99%